2020
DOI: 10.1038/s41598-020-59496-0
|View full text |Cite
|
Sign up to set email alerts
|

RNA sequence and length contribute to RNA-induced conformational change of TLS/FUS

Abstract: Translocated in liposarcoma (TLS)/fused in sarcoma (FUS) is a multitasking DNA/RNA binding protein implicated in cancer and neurodegenerative diseases. Upon DNA damage, TLS is recruited to the upstream region of the cyclin D1 gene (CCND1) through binding to the promotor associated non-coding RnA (pncRnA) that is transcribed from and tethered at the upstream region. Binding to pncRnA is hypothesized to cause the conformational change of TLS that enables its inhibitive interaction with histone acetyltransferases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 36 publications
(43 reference statements)
0
13
0
Order By: Relevance
“…4 a). We had already revealed that this spectrum change reflects the compact-to-extended conformational change of FUS with pncRNA on the basis of FRET and HS-AFM analyses 23 , 24 . When further strokes of pipetting were applied, however, the spectrum rarely changed, if any (Fig.…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…4 a). We had already revealed that this spectrum change reflects the compact-to-extended conformational change of FUS with pncRNA on the basis of FRET and HS-AFM analyses 23 , 24 . When further strokes of pipetting were applied, however, the spectrum rarely changed, if any (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…In our previous studies, we showed that full-length (602 nucleotide residues) and fragments of pncRNA (Supplementary Fig. S1 ) can induce a conformational change of FUS 23 , 24 . Interestingly, this time we found that the reduction in the fluorescence intensity caused by shear stress on pipetting was not observed when full-length pncRNA was added to the FUS fusion protein (Fig.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations